Atos de currículo no aprenderensinar Matemática com dispositivos móveis - Oliveira, Elisânia Santana de (2024)
The main objective of this thesis was to understand how applications on mobile devices can contribute to the creation of curriculum acts in Mathematics. Therefore, this investigation is justified by the contemporary socio-technical scenario, with the power of digital cultures, especially with the use of applications on mobile devices, transforming social behaviors and even affecting the educational environment by modifying the way in which students interact. they relate and seek knowledge. The research is based on the epistemology of multireferentiality to understand educational issues from multiple perspectives and has a qualitative approach. Research-training with digital cultures was the theoretical-methodological support adopted in the investigation, as training processes were seen as constituting an intention of the research that was developed in social contexts marked by the power of digital cultures. The social actors were 24 students from an integrated high school class at IFS/Campus Itabaiana. As data production devices, interactive observation was adopted – recording the affective and imaginary aspects and learning observed during the study; image and video records – record moments of the research; online questionnaires – prior assessment of the participants' relationship with the applications and identification of conceptions about the research actions; app-research diaries – critical and detailed record of the experience lived in the investigation; Study Group on Mathematics Teaching with Mobile Digital Technologies (Em@tec) and “Mais Formação” – training environments aimed at developing pedagogical actions in order to observe possible curriculum acts in Mathematics using applications on mobile devices. The empirical research corpus was analyzed using critical hermeneutics, with which we sought to identify three underlying notions that represent the knowledge and meanings constructed about the investigation. The notion of intercritical experiential knowledge with applications on mobile devices emerged above all from the mathematical experiences experienced with the use of applications on mobile devices in “Mais Formação” and plural formative processes in Learning to Teach Mathematics was shown in the multiple learning strategies used during the activities developed in this same training environment. The notion of multi-referential curriculum acts in a network indicated the resignification of training processes by social actors by expressing an implication with learning in meaning, referenced in experience, as they sought to deepen their knowledge about financial mathematics. In this sense, the findings reveal that applications on mobile devices enhance the creation of curriculum acts in Mathematics, contributing to the redefinition of learning-teaching within the scope of this discipline and intervening in the curricular field and training.